Flood Level Detection System using Ultrasonic Sensor and ESP32 Camera: Preliminary Results - Hamzah, Shipun Anuar; Dalimin, Mohd Noh; Md Som, Mohamad; Zainal, Mohd Shamian; Ramli, Khairun Nidzam; Sanusi@Ikhsan, Mohd Hamim; Yusop, Azli; Ishak, Maizul; Abd Rahman, Ramhuzaini; Sidek, Azmi; Utomo, Wahyu Mulyo; Abd Jamil, Ansar; et al. (semarak ilmu, 2024)
An efficient flood detection system needs to be developed immediately due to the frequency of floods in areas where visitors are concentrated in Malaysia, especially during the monsoon season or when there is heavy rain that makes it difficult for authority to pass on flood information to visitors. Among them is Taman Negara Endau Rompin (Selai) Johor which experiences flooding every monsoon season. However, the method of distributing flood information to visitors still need to be improved in terms of speed, accuracy and systematic. Apart from the factors of location and distance, the main challenge to detect floods is the lack of manpower and real time flood detection system. The conventional method is through patrols or the staff on duty at the counter receiving phone calls from the surrounding residents informing them of flooding is less effective and needs to be improved. Initially, the work of identifying the actual flood area, selecting the installation location of the system and measuring the strength of the telco signal coverage was done with the help of the authority. This article proposes a prototype to detect river water level, temperature, humidity, flood images and send flood notifications to users via smartphones in real time. The device consists of an RTU unit, a sensor arm and IoT system. The work incorporates a Pi microcontroller, a WIFI network equipped with digital camera and industrial sensors. This prototype is able to provide consistent flood data readings to the users. In addition to data readings and flood images displayed in the GUI (web monitoring), flood readings and images are also sent to the authorities via the Telegram channel. TNB electricity supply is used as the source while the authorities and visitors can access the data through their respective smartphones. A prototype has been developed and tested to see the stability, consistency and accuracy of its operation while the data received is stored in the database. This system is expected to help officers channel flood information to visitors at the visitor reception desk in a more organized and systematic manner.